2016
DOI: 10.1002/iub.1477
|View full text |Cite
|
Sign up to set email alerts
|

CacyBP/SIP inhibits Doxourbicin‐induced apoptosis of glioma cells due to activation of ERK1/2

Abstract: Calcyclin-binding protein or Siah-1-interacting protein (CacyBP/SIP) was previously reported to promote the proliferation of glioma cells. However, the effect of CacyBP/SIP on apoptosis of glioma is poorly understood. Here, our study shows that CacyBP/SIP plays a role in inhibiting doxorubicin (DOX) induced apoptosis of glioma cells U251 and U87. Overexpression of CacyBP/SIP obviously suppressed the DOX-induced cell apoptosis. On the contrary, silencing of CacyBP/SIP significantly promoted it. Further investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…As Cacybp is an E3 ubiquitin ligase, we hypothesized that the 46 downregulated genes may include ubiquitinated substrates of Cacybp. The current focus of research is mainly Cacybp nuclear transfer (11,13,21,22) and phosphorylation activities (23)(24)(25)(26), which is consistent with our results. Using Cytoscape software we identified biological processes and molecular functions that may be affected by Cacybp.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As Cacybp is an E3 ubiquitin ligase, we hypothesized that the 46 downregulated genes may include ubiquitinated substrates of Cacybp. The current focus of research is mainly Cacybp nuclear transfer (11,13,21,22) and phosphorylation activities (23)(24)(25)(26), which is consistent with our results. Using Cytoscape software we identified biological processes and molecular functions that may be affected by Cacybp.…”
Section: Discussionsupporting
confidence: 91%
“…We identified genes closely related to Cacybp expression through bioinformatics software analysis, but determining which of these differential genes are targets of Cacybp and which are ubiquitinated substrates requires further study. The current focus of research is mainly Cacybp nuclear transfer (11,13,21,22) and phosphorylation activities (23)(24)(25)(26), which is consistent with our results. In addition, we also found that Cacybp is involved in cell secretion and examined Cacybp expression in glioma patients and its relationship with prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, our group focused on the V protein mediated host apoptosis. CacyBP/SIP was reported to participate in apoptosis (Chen et al, 2013 ; Fu et al, 2016 ; Tang et al, 2016 ). Among the 30 clones identified, four clones corresponded to CacyBP/SIP, we chose it for further study due to its involvement in the cell apoptosis adjustment.…”
Section: Resultsmentioning
confidence: 99%
“…CacyBP/SIP is involved in protein de-phosphorylation, ubiquitination, cytoskeletal dynamics, and all of these functions have been implicated in a wide range of cellular processes, such as cell proliferation, tumorigenesis, cell differentiation and gene expression (Shi et al, 2014 ; Topolskawoś et al, 2016 ). In some tumor cells, CacyBP/SIP has been shown to be involved in cell apoptosis, but the promotion or suppression of cancer apoptosis by CacyBP/SIP may depend on cell type (Chen et al, 2013 ; Fu et al, 2016 ; Tang et al, 2016 ). The role of CacyBP/SIP in DF-1 cell apoptosis and the effects of CacyBP/SIP on NDV replication efficiency in these cells remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to cancer, apoptosis has become a popular target for many treatment strategies as there is a close relationship with apoptosis and many of the processes involved in cancer progression [2227]. …”
Section: Resultsmentioning
confidence: 99%